Produção de sementes do capim-braquiária submetido à irrigação e doses de nitrogênio - Pancera Júnior, Edson José (2011)
The objective of the experiment was to evaluate the effects from irrigation (control and irrigated), doses of N (0, 25, 50 or 75 kg ha-1), and harvesting time (January and May) on the seed production of Signalgrass (Urochloa decumbens ( Basilisk) in Umuarama, Northwestern Paraná, Brazil. The experimental design was the Split-plot arrangement of treatments with three blocks completely random. It was evaluated the dry biomass of the plants at the harvesting time, the harvesting index, production of apparent and pure seeds, and relationships between seed yield components with seed yield. The number of tillers with racemes showed effects for dose of N. The yields of apparent and pure seeds increased with the doses of N. The quantity of dry matter, apparent and pure seeds were higher in January than in May. The current responses indicated no influence of the irrigation on pure seeds yield. In January and May, the yield of apparent seeds was 2022, and the yield of pure seeds was 868 kg ha-1 estimated from the non-irrigated plots fertilized with N at 75 kg ha-1. The current yield of pure seeds of Signalgrass in Brazil can be improved by the application of nitrogen.